Preliminary standards for the Psychomotor Development Test (TEPSI) for Argentine children aged 3-4 - Espósito, Adriana V. L. (2018)
The goals of this study are to develop local standards for the TEPSI Psychomotor Development Test for Argentine children and to contrast the level of psychomotor development and its growth rate between the Argentine and Chilean samples used for standardization of the instrument. Two hundred and five children aged 3 to 5 years attending public daycare centers in the province of Mendoza were evaluated. The internal consistency of the test was addressed and item-subtest correlations were calculated. Additionally, an analysis of variance (ANOVA) with a priori contrast was used, T-scores per age group were calculated, and Cohen’s d was estimated to assess the magnitude of the differences found between the contrasted samples. The TEPSI displayed adequate psychometric properties as well as high sensitivity to assess age differences in children’s psychomotor development. Argentine pre-school children showed better psychomotor performance when compared to their Chilean peers, in a context where both groups displayed different developmental rates. These results highlight the importance of developing updated TEPSI local standards that consider the socio-cultural features of each country, with a view to obtaining an accurate and reliable assessment of children’s psychomotor development.